Kesenian Wayang Kulit Sebagai Sarana Publikasi Sejarah dalam Penyebaran Islam di Jawa - Anjani, Fitria Nungki; Fahruddin (Institut Agama Islam Negeri Ponorogo, 2024)
Wayang is a cultural heritage of the ancestors of the Indonesian people which is estimated to have existed since ±1500 years BC. In Java, shadow puppets are used and utilized to spread the preaching of Islamic teachings. The spread of Islam in Java is inseparable from the role of the Wali Sango in spreading Islamic teachings. Thanks to the saints Islam was able to flourish in the life of society. This study aims to, (1) know the history of shadow puppets, (2) explain the role of wayang kuit as a medium for spreading Islam in Java, (3) explain the spread of Islam in Java, (4), know the role of walisanga in spreading Islam in Java. This type of research uses qualitative descriptive methods. The conclusion that can be drawn is that wayang has been around since before the existence of Hindhu Buddhism, in its development shadow puppets were used for the spread of Islam, especially on the island of Java. In its dissemination, there is a role of walisangas, one of which is Sunan Kalijaga who spread Islamic teachings with the media of Wayang Kulit.